Deformation Study of Strongly Structured Clays Considering Damage Effects - Yansong Shi; Bin Tang; Yinchuan Wang; Yanhua Xie (Applied Sciences)
Settlement values calculated per the current “Code for Design of Building Foundations” demonstrate significant discrepancies when compared to the actual measured settlement values observed after disturbing a strong, cohesive soil foundation. This inconsistency introduces uncertainties in engineering design. To investigate the deformation behavior of highly structured clay, which is particularly sensitive to disturbances, this study employed a shaking table to subject undisturbed soil samples to various disturbance levels. The shaking frequencies were set at 20 Hz, 35 Hz, and 50 Hz, with durations of 30, 60, 90, and 120 min. One-dimensional compression tests were performed to examine the relationship between soil deformation parameters and overburden pressure, alongside an analysis of the deformation process and pore structure damage in the highly structured clay. A fitting process using Origin software was utilized to develop a deformation modulus calculation model that accounted for disturbance and damage effects, aiming to enhance the accuracy of foundation settlement predictions. The results indicate that the proposed empirical formula for the deformation modulus is highly reliable, which is essential for improving the precision of foundation settlement calculations and ensuring engineering safety.